Predictors of Drug Treatment Resistance in Obsessive Compulsive Disorder - Ünverdi Bıçakçı, E.; Özyıldız Güz, H.; Şahin, A.R.; Böke, Ö.; Sarísoy, G.; Karabekİroğlu, A.; Civan Kahve, A.C. (Cukurova University, Faculty of Medicine Balcali/ADANA 01330, 2019)
Objective: The aim of this study is to investigate the predictive factors related to pharmacotherapy resistance in patients with obsessive-compulsive disorder (OCD). Methods: Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), Structured Clinical Interview for DSM-III-R Axis II Disorders (SCID-II), Yale-Brown Obsessive Compulsive Scale-Symptoms Checklist (YBOCS), Hamilton Depression Rating Scale (HDRS), Childhood Trauma Questionnaire (CTQ), Dissociative Experiences Scale, Level of Expressed Emotion were applied to 30 treatment resistant patient with OCD and 30 treatment responder patients with OCD. Expressed Emotion Scale (EES) were applied to the relatives of patients. Results: When the groups were compared, living out of city center, age of onset in disease, total disease duration and presence of psychiatric disease in the family, YBOCS, HDRS, OVIS, EES, CTQ sexual abuse scale scores and major depression comorbidity were significantly higher in treatment resistant group. High YBOCS total score and presence of mental illness in the family were found to be effective for predicting resistance to drug treatment. Conclusion: The high severity of the disease and the presence of psychiatric dis-eases in the family increase the risk of treatment resistance. (Anatolian Journal of Psychiatry 2019; 20(6):565-572). © 2019, (publisher name). All Rights Reserved.
Obsesif Kompulsif Bozuklukta İlaç Tedavisine Direncin Yordayıcıları
Keywords: Obsessive Compulsive Disorder; Predictor; Resistant; Treatment